A implantação da televisão digital no Brasil e no Chile: Tendências e assimetrias - Marques De Carvalho, Juliana [UNESP] (Pontificia Universidad Catolica de Chile, 2013)
The digitalization of television is a tendency observed in many countries around the world. In Latin America much has been discussed about its implementation, in Brazil is already instituted the Brasilian System of Digital Television and in Chile the Digital Television (TVD), in this way the present article has the objective of comparing the main aspects of the digital television implementation between Brazil and Chile, emphasizing the theoretical matrices observed in this process.
The implantation of digital television in Brazil and Chile: Tendencies and asymmetries
Keywords: Brazil; Chile; Communication Policy; Digital Culture; Digital television